Small-Molecule Bi-DOTA Complex for High-Performance CT and Spectral CT Bioimaging - Dai, Guidong; Zhang, Yu; Wang, Ximei; Wang, Xingyu; Jia, Juan; Jia, Fei; Yang, Lu; Yang, Chunmei (Frontiers in Oncology, 2022)
Objectives: It’s necessary to develop a high-performance and biocompatible contrast agent for accurate diagnosis of various diseases via in vivo computed tomography (CT) imaging. Here, we synthesized a small molecular Bi-DOTA complex as a high-performance contrast agent for in vitro and in vivo CT bioimaging. Materials and Methods: In our study, Bi-DOTA was fabricated through a facile and one-pot synthesis strategy. The formed Bi-DOTA complex was characterized via different techniques. Furthermore, Bi-DOTA was used for in vitro and in vivo CT bioimaging to verify its X-ray attenuation ability, especially in vivo kidney imaging, gastrointestinal tract CT imaging and spectral CT imaging. Results: A small molecular Bi-DOTA complex with a molecular mass of 0.61 kDa was synthesized successfully, which exhibited outstanding dispersion, good biocompatibility and superior X-ray attenuation ability. Meanwhile, we showed that the obtained contrast agent was quite biocompatible and safe in the given concentration range as confirmed by in vitro and vivo cytotoxicity assay. Besides, the proposed contrast agent can be rapidly excreted from body via urinary system, avoiding the potential side effects caused by the long-term retention in vivo. Importantly, Bi-DOTA was successfully used in high-quality in vitro CT imaging, in vivo kidney imaging, gastrointestinal tract CT imaging and spectral CT imaging. Conclusions: These superiorities allowed Bi-DOTA to be used as an efficient CT contrast agent and laid down a new way for the design of high-performance CT contrast agents with great clinical transformation potential.